A high-strength wear-resistant polyethylene gas pipeline and preparation method thereof
By using modified materials and processes such as high-density polyethylene, high-strength wear-resistant polyethylene gas pipelines are prepared, which solves the problem of insufficient wear and pressure resistance of existing pipelines, and achieves higher performance and longer use service life.
Patent Information
- Application Number
- CN202411571769.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2044-11-06
AI Technical Summary
The wear resistance and pressure resistance of existing polyethylene gas pipelines are poor, making it difficult to meet the needs of long-distance construction, long-term friction and high-pressure environments.
High-density polyethylene, modified ethylene propylene ternary rubber, modified chlorinated polyethylene rubber, modified basalt fiber, silicon carbide ceramic material, magnesium oxide, lubricant, hindered amine light stabilizer, hindered phenol antioxidant, Antistatic agents and other materials are compounded in a certain proportion, and high-strength wear-resistant polyethylene gas pipelines are prepared through process steps such as mixing, refining, and extrusion.
It significantly improves the compressive strength, impact resistance and wear resistance of the pipeline, extends the service life, is suitable for use in various harsh environments, and meets the needs of high, medium and low pressure gas transportation.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a high-strength wear-resistant polyethylene gas pipeline and a preparation method thereof. Background Art
[0002] With the continuous development and progress of society, gas, as an efficient and clean energy, plays an increasingly important role in people's daily life and industrial production. As an important carrier for transporting gas, the technical level of gas pipelines is directly related to the safe and stable supply of gas.
[0003] Commonly used gas pipeline materials include cast iron pipes, steel pipes, polyethylene pipes, etc. Cast iron pipes were once one of the main materials for gas pipelines, but due to their heavy weight, high construction difficulty, poor corrosion resistance and other disadvantages, they have gradually been replaced by steel pipes and polyethylene pipes. Steel pipes have the advantages of high strength, wear resistance, and good pressure resistance, but they are also relatively heavy and have relatively poor corrosion resistance. They are easily corroded by gas (corrosive components such as hydrogen sulfide, etc.) and the environment. If anti-corrosion measures are taken, the cost will increase significantly. Therefore, more and more polyethylene pipes are used to transport gas in the market. Polyethylene pipes have the advantages of light weight, corrosion resistance, and simple construction. They are widely used in medium and low pressure gas transportation, especially civil gas transportation.
[0004] However, due to the performance limitations of the material itself, the existing polyethylene pipes still have the following problems:
[0005] (1) Poor wear resistance: During the installation of the pipeline, it usually rubs against the ground, other construction materials or tools. If the pipeline does not have good wear resistance, it is easy to be scratched and worn during operations such as dragging and laying, thereby reducing the strength and sealing of the pipeline. The buried polyethylene gas pipeline will move relative to the surrounding soil. Especially in the case of soil settlement, geological activities, etc., long-term micro-friction will gradually damage the surface of the pipeline. If the wear resistance of the pipeline is insufficient, it will be damaged, causing gas leakage and causing safety accidents. When the gas flows in the pipeline, it will have a certain scouring effect on the inner wall of the pipeline. Although the flow rate of gas is usually relatively low, it will also cause wear on the inner wall of the pipeline after long-term operation. Especially in some cases where the pressure fluctuations are large or the flow changes frequently, the scouring effect will be more obvious.
[0006] (2) Poor pressure resistance: Gas will generate a certain amount of pressure when it is transmitted in the pipeline. Polyethylene gas pipelines need to have sufficient strength to withstand this internal pressure to ensure that they will not break or deform under normal working pressure. If the strength is insufficient, leakage will occur under the action of pressure, which will not only waste gas resources, but also bring safety hazards, such as causing fires, explosions and other dangerous situations. Buried polyethylene gas pipelines must withstand the covering pressure from the soil above. As the burial depth increases, the soil pressure will also increase accordingly. Low-strength pipelines are prone to deformation, affecting gas transportation. In the pipeline laying area, there may be external loads generated by construction activities or vehicle traffic. Low-strength polyethylene gas pipelines are difficult to withstand these accidental external forces and are easily damaged by external loads.
[0007] Polyethylene gas pipelines with good wear resistance can better resist the influence of various wear factors, thereby extending the service life of the pipeline. This can not only reduce the replacement and maintenance costs of the pipeline, but also ensure the stability and safety of the gas supply. In the long run, wear resistance is an important guarantee for polyethylene gas pipelines to maintain good performance throughout their entire service life. High-strength and pressure-resistant polyethylene gas pipelines have better reliability and durability. In the long-term use process, they can withstand the test of various complex environments and working conditions, reduce the frequency of maintenance and replacement caused by pipeline strength problems, thereby reducing maintenance costs and ensuring the long-term safety and stability of gas supply. Therefore, wear resistance and pressure resistance are indicators that polyethylene pipelines urgently need to improve. It is necessary to continuously strengthen the research and development of pipeline materials, improve performance, ensure the safety of gas transportation, and be suitable for a wider range of use environments, and even meet the higher requirements of high-pressure gas transportation, especially the transportation of gas in industrial production. Summary of the invention
[0008] The existing polyethylene pipes have poor wear resistance and pressure resistance, and cannot meet the problems of long-distance construction, long-term friction and high-pressure environment use. The present invention provides a high-strength wear-resistant polyethylene gas pipeline and a preparation method thereof, which uses high-density polyethylene, modified EPDM rubber, modified chlorinated polyethylene rubber, modified basalt fiber, silicon carbide ceramic material, magnesium oxide, lubricant, hindered amine light stabilizer, hindered phenol antioxidant, antistatic agent and the like as raw materials and compounded in a certain proportion; and according to the properties and dispersion characteristics of each component material, the mixing, mixing, extrusion and other process steps and parameters are designed, which can well realize the production of pipelines and obtain gas pipelines with uniform quality and excellent performance. It can greatly improve the compressive strength, impact resistance and wear resistance of the pipeline, and effectively improve the weather resistance of the pipeline, comprehensively improve the performance and service life of the pipeline, and is more suitable for use in various harsh environments. It can meet the needs of long-distance construction, long-term friction and high-pressure environment use, and can be widely used in high, medium and low pressure gas transportation, civil and industrial gas transportation. Its specific technical scheme is as follows:
[0009] A high-strength wear-resistant polyethylene gas pipeline comprises the following raw materials in parts by weight: 75 to 85 parts of high-density polyethylene, 6 to 10 parts of modified EPDM rubber, 3 to 5 parts of modified chlorinated polyethylene rubber, 8 to 12 parts of modified basalt fiber, 5 to 8 parts of silicon carbide ceramic material, 0.2 to 0.6 parts of magnesium oxide, 1.2 to 2 parts of lubricant, 0.2 to 0.5 parts of hindered amine light stabilizer, 0.1 to 0.5 parts of hindered phenol antioxidant, 0.5 to 1 part of antistatic agent; the modified EPDM rubber is an EPDM rubber modified by polyurethane, maleic anhydride grafted polymer and dioctyl phthalate; the modified chlorinated polyethylene rubber is a chlorinated polyethylene rubber modified by polyurethane, maleic anhydride grafted polymer and dioctyl phthalate; the modified basalt fiber is a basalt fiber with a composite surface modified by carbon black, potassium titanate whiskers, fumed silica and propylene glycol laurate.
[0010] Among the above raw materials, the index of the high-density polyethylene is: density 0.949g / cm 3 ~0.965g / cm 3 , crystallinity 80%~90%, softening point 125℃~135℃.
[0011] Among the above raw materials, the lubricant includes calcium stearate, zinc stearate and silicone powder, and the mass ratio is calcium stearate: zinc stearate: silicone powder = (2-5): (1-3): (1-3).
[0012] Among the above raw materials, the silicon carbide ceramic material is a powder obtained by crushing waste silicon carbide ceramics to obtain a particle size of less than 50 μm; the particle size of the magnesium oxide is less than 50 μm.
[0013] Among the above raw materials, the preparation method of the modified EPDM rubber comprises the following steps: according to the mass ratio, EPDM rubber: polyurethane: maleic anhydride grafted polymer: dioctyl phthalate = (90-100): (6-12): (1-5): (5-10), EPDM rubber, polyurethane, maleic anhydride grafted polymer and dioctyl phthalate are mixed at 65°C-75°C to obtain modified EPDM rubber.
[0014] Among the above raw materials, the preparation method of the modified chlorinated polyethylene rubber comprises the following steps: according to the mass ratio, chlorinated polyethylene rubber: polyurethane: maleic anhydride grafted polymer: dioctyl phthalate = (90-100): (5-10): (1-5): (8-12), chlorinated polyethylene rubber, polyurethane, maleic anhydride grafted polymer and dioctyl phthalate are mixed at 85°C-95°C to obtain modified chlorinated polyethylene rubber.
[0015] Among the above raw materials, the preparation method of the modified basalt fiber comprises the following steps: according to the mass ratio, basalt fiber: carbon black: potassium titanate whisker: fumed silica: propylene glycol laurate = (90-100): (1-3): (0.4-0.8): (2-5): (3-5), firstly, the potassium titanate whisker and the fumed silica are evenly mixed by air flow, and then the carbon black is added, and the air flow mixing is continued until it is uniform to obtain an auxiliary material; the propylene glycol laurate is diluted to 4 to 5 times the mass with ethanol to obtain a ball milling aid; the basalt fiber and the ball milling aid are wet-milled for 10 to 15 minutes, and then the auxiliary material is added, and the wet ball milling is continued for 10 to 20 minutes, and the material is discharged, and the ethanol is removed by drying to obtain the modified basalt fiber.
[0016] In the above-mentioned method for preparing modified basalt fiber, the diameter of the basalt fiber ranges from 10 μm to 30 μm, and the length ranges from 1 mm to 3 mm.
[0017] In the above-mentioned method for preparing modified basalt fiber, the particle sizes of the carbon black, potassium titanate whiskers and fumed silica are all nanometer-level.
[0018] The above-mentioned method for preparing a high-strength wear-resistant polyethylene gas pipeline comprises the following steps:
[0019] S1: mixing silicon carbide ceramic material, magnesium oxide and lubricant according to weight proportions to obtain a mixture A;
[0020] S2: Mixing the hindered amine light stabilizer, the hindered phenol antioxidant and the antistatic agent according to their weight percentage to obtain a mixture B;
[0021] S3: Dry the high-density polyethylene to remove moisture; add the high-density polyethylene, modified EPDM rubber, modified chlorinated polyethylene rubber, and mixture A into an internal mixer according to the mass fraction, and perform internal mixing at 140°C to 160°C, with a rotation speed of 60r / min to 80r / min, for 5min to 10min, then add the modified basalt fiber and mixture B, perform internal mixing at 160°C to 180°C, with a rotation speed of 100r / min to 120r / min, for 15min to 20min, and obtain the internal mixing material, and extrude and shape it through a single-screw or twin-screw extruder, and air-cool it to obtain a shaped pipe;
[0022] S4, placing the shaped pipe at 50℃~60℃ and leaving it to stand for 24h~30h to obtain a finished pipe.
[0023] In S3 of the above preparation method, the drying temperature is 80° C. to 95° C., and the drying time is 4 h to 6 h.
[0024] In S4 of the above preparation method, the extruder is divided into a feeding zone, a compression zone, a metering zone and a head zone: the temperature of the feeding zone is 140°C to 150°C, the temperature of the compression zone is 170°C to 180°C, the temperature of the metering zone is 160°C to 170°C, and the temperature of the head zone is 150°C to 160°C; the extrusion speed of the extruder is 0.5m / min to 1.5m / min.
[0025] The high-strength wear-resistant polyethylene gas pipeline and the preparation method thereof provided by the present invention have the following beneficial effects compared with the prior art:
[0026] 1. The pipeline of the present invention adopts high-density polyethylene, modified EPDM rubber, modified chlorinated polyethylene rubber, modified basalt fiber, silicon carbide ceramic material, magnesium oxide, lubricant, hindered amine light stabilizer, hindered phenol antioxidant, antistatic agent and the like as raw materials; each component is used in a certain proportion to greatly improve the compressive strength, impact resistance and wear resistance of the pipeline, and effectively improve the weather resistance of the pipeline, comprehensively improve the performance and service life of the pipeline, and is more suitable for use in various harsh environments.
[0027] Second, the present invention uses appropriate amounts of polyurethane, maleic anhydride grafted polymer and dioctyl phthalate to modify EPDM rubber. Polyurethane can increase the hardness and strength of rubber, so that it can withstand greater external forces. Polyurethane can also improve the heat resistance temperature of EPDM rubber to a certain extent, thereby improving the performance of pipelines. Maleic anhydride grafted polymer can form chemical bonds with EPDM rubber, enhance the bonding force between rubber molecules, thereby improving the tensile strength and tear strength of rubber. In addition, maleic anhydride grafted polymer can also improve the mixing and fusion of EPDM rubber and high-density polyethylene, reduce phase separation at high temperatures, thereby improving the heat resistance of rubber and improving the performance of pipelines. Dioctyl phthalate can increase the toughness of rubber, absorb energy when rubber is subjected to external force, reduce the generation and expansion of cracks, and make it difficult to break when subjected to impact. In addition, dioctyl phthalate can reduce the viscosity of EPDM rubber, thereby improving the mixing and fusion of EPDM rubber and high-density polyethylene, making it easier to flow and shape during processing, thereby improving the performance of pipeline use. The present invention adopts maleic anhydride grafted polymer and dioctyl phthalate for modification, which can compositely enhance the compatibility of EPDM rubber with other materials, making EPDM rubber easier to disperse evenly when blended with other materials, and improving processing efficiency and product quality. The present invention adopts polyurethane and dioctyl phthalate for modification in a certain proportion, which can well balance the strength, toughness and wear resistance of EPDM rubber and high-density polyethylene, and further improve toughness and wear resistance while effectively enhancing hardness and strength.
[0028] In addition, polyurethane and maleic anhydride grafted polymers can form a protective film on the rubber surface to prevent chemical erosion and enhance corrosion resistance. EPDM rubber itself has good chemical resistance. By adding these modifiers, it can further improve corrosion resistance, aging resistance, and weather resistance, and expand the application range of pipelines.
[0029] 3. The present invention uses appropriate amounts of polyurethane, maleic anhydride grafted polymer and dioctyl phthalate to modify chlorinated polyethylene rubber. Polyurethane can form a cross-linked structure in the rubber system, enhance the bonding force between molecules, and thus give the chlorinated polyethylene rubber higher tensile strength and tear strength. Polyurethane has high heat resistance and can transfer part of its heat resistance to the chlorinated polyethylene rubber, thereby improving the heat-resistant temperature of the rubber. Maleic anhydride grafted polymer can react chemically with the chlorinated polyethylene rubber to form a strong chemical bond, further improving the mechanical strength and chemical resistance of the rubber. Maleic anhydride grafted polymer can improve the compatibility of rubber with other materials, reduce the phase separation phenomenon at high temperature, thereby enhancing the heat resistance stability of the chlorinated polyethylene rubber, making the rubber easier to disperse evenly during the blending process, and ensuring the consistency of product quality. Dioctyl phthalate can increase the toughness of the rubber, making the rubber less likely to break when impacted, and improving its impact resistance. Dioctyl phthalate can reduce the viscosity of the chlorinated polyethylene rubber, making it easier to flow and form during processing, and improving processing efficiency. The combination of polyurethane and maleic anhydride grafted polymer can form a protective layer on the rubber surface to block the erosion of chemical substances, thereby improving the corrosion resistance and weather resistance of the pipeline. The present invention adopts maleic anhydride grafted polymer and dioctyl phthalate for modification, which can compositely enhance the compatibility of chlorinated polyethylene rubber with other materials, making it easier to disperse chlorinated polyethylene rubber evenly when blended with other materials, thereby improving processing efficiency and product quality. The present invention adopts polyurethane and dioctyl phthalate for modification in a certain proportion, which can well balance the strength, toughness and wear resistance of chlorinated polyethylene rubber and high-density polyethylene, and further improve toughness and wear resistance while effectively enhancing hardness and strength.
[0030] 4. The present invention uses carbon black, potassium titanate whiskers, fumed silica and propylene glycol laurate to carry out composite surface coating modification on basalt fiber. Carbon black coating modification can increase the hardness and strength of basalt fiber. Carbon black particles form a tiny reinforcing structure on the fiber surface, which can withstand greater external forces and improve the tensile strength and bending resistance of the fiber. Carbon black has good heat resistance and remains stable at high temperatures. The presence of carbon black can increase the heat resistance temperature of basalt fiber, so that it can still maintain good mechanical properties and dimensional stability under high temperature environment. Potassium titanate whiskers have high strength and rigidity, which can effectively enhance the mechanical properties of basalt fiber. The three-dimensional network structure formed by whiskers on the fiber surface can disperse external forces and reduce stress concentration, thereby improving the strength and toughness of the fiber. Potassium titanate whiskers have a high melting point and thermal stability, and maintain the stability of their structure and performance at high temperatures. The addition of potassium titanate whiskers can improve the heat resistance of basalt fiber, so that it can be used at higher temperatures. Fumed silica can fill the tiny pores and defects on the fiber surface, making the fiber surface smoother and denser, and improving the strength and wear resistance of the fiber. Fumed silica can also improve the heat resistance of basalt fiber. Basalt fiber itself has a certain toughness. The present invention uses carbon black, potassium titanate whiskers and fumed silica to carry out composite surface coating modification on basalt fiber, which can further improve its toughness. The synergistic effect of carbon black, potassium titanate whiskers and fumed silica can absorb energy when the fiber is subjected to external force, reduce the generation and expansion of cracks, and improve the impact resistance, fracture toughness and wear resistance of the fiber. The presence of carbon black, potassium titanate whiskers and fumed silica can increase the surface roughness of basalt fiber, improve the interfacial bonding force between the fiber and rubber and polyethylene components, and the rough surface can increase the mechanical intercalation between the fiber and other components, improve the bonding strength of the interface, thereby improving the mechanical properties of the composite material. Propylene glycol laurate can form a film on the surface of basalt fiber, reduce the friction coefficient, reduce friction and wear, and improve the wear resistance and durability of basalt fiber and pipes.
[0031] In addition, the present invention uses fumed silica to pre-mix and disperse potassium titanate whiskers and carbon black. Fumed silica has a good dispersing effect on potassium titanate whiskers and carbon black, making the ball-milled mixed coating distribution of potassium titanate whiskers and carbon black more uniform, thereby reducing weak parts and comprehensively improving pipeline performance. Propylene glycol laurate is used to prepare a ball milling aid, which can also effectively improve the homogeneity of ball milling mixed coating, better disperse potassium titanate whiskers and carbon black, and improve the modified quality of basalt, with better modified homogeneity; it can also help the dispersion homogeneity of basalt fiber in rubber and polyethylene, and the mixing quality is more uniform, which can effectively reduce the generation of weak parts of the pipeline and comprehensively improve pipeline performance. The present invention uses fumed silica and propylene glycol laurate in a certain proportion for wet ball milling, which has a synergistic effect, can better improve the uniformity of modified distribution, and improve pipeline homogeneity. In addition, the present invention uses carbon black, potassium titanate whiskers, fumed silica and propylene glycol laurate to perform composite surface coating modification on basalt fiber, which can reduce the amount of auxiliary agents (coating agents) used, reduce the cost of materials, and at the same time enable the pipeline to achieve excellent mechanical properties.
[0032] 5. The combination of magnesium oxide and silicone powder has a good effect on enhancing the mechanical properties of rubber and polyethylene plastics. Magnesium oxide can act as a cross-linking agent in rubber, increase the bonding force between rubber molecules, and thus improve the mechanical properties of rubber such as tensile strength and tear strength. Magnesium oxide has high thermal stability and can improve the heat resistance temperature of the pipeline to a certain extent. Silicone powder has good lubricity and dispersibility, which can make various fillers in rubber evenly dispersed, further enhancing the strength of rubber. Silicone powder can form a protective film on the surface of rubber to prevent heat transfer and oxygen penetration, further improving the heat resistance of the pipeline. The combination of magnesium oxide and silicone powder can improve the hardness and wear resistance of rubber and polyethylene plastics, reduce the wear of rubber and polyethylene plastics during use, and extend the service life of the pipeline. The combination of the two can also improve the impact resistance of the pipeline and reduce the rupture and damage of the pipeline when it is impacted.
[0033] 6. The present invention designs the process steps and parameters of mixing, mixing, extrusion, etc. according to the properties and dispersion characteristics of each component material, which can well realize the production of pipelines and obtain gas pipelines with uniform quality and excellent performance. The gas pipeline can meet the requirements of long-distance construction, long-term friction and high-pressure environment use, and can be widely used in high, medium and low pressure gas transportation, civil and industrial gas transportation. DETAILED DESCRIPTION
[0034] The present invention is further described below in conjunction with specific implementation cases, but the present invention is not limited to these embodiments.
[0035] Example 1
[0036] A high-strength wear-resistant polyethylene gas pipeline comprises the following raw materials in parts by mass: 80 parts of high-density polyethylene, 8 parts of modified EPDM rubber, 4 parts of modified chlorinated polyethylene rubber, 10 parts of modified basalt fiber, 6.5 parts of silicon carbide ceramic material, 0.4 parts of magnesium oxide, 1.6 parts of lubricant, 0.3 parts of hindered amine light stabilizer, 0.3 parts of hindered phenol antioxidant, and 0.8 parts of antistatic agent.
[0037] Among them, the indicators of high-density polyethylene are: density 0.954g / cm 3 , crystallinity 85.2%, softening point 128°C. The lubricant includes calcium stearate, zinc stearate and silicone powder, and the mass ratio is calcium stearate: zinc stearate: silicone powder = 3:2:2. The silicon carbide ceramic material is a powder with a particle size of less than 50 μm obtained by crushing waste silicon carbide ceramics; the particle size of the magnesium oxide is less than 50 μm.
[0038] Among them, the preparation method of modified EPDM rubber includes the following steps: according to the mass ratio of EPDM rubber: polyurethane: maleic anhydride grafted polymer: dioctyl phthalate = 95:9:3:8, EPDM rubber, polyurethane, maleic anhydride grafted polymer and dioctyl phthalate are mixed at 70°C to obtain modified EPDM rubber.
[0039] Among the above raw materials, the preparation method of the modified chlorinated polyethylene rubber comprises the following steps: according to the mass ratio of chlorinated polyethylene rubber: polyurethane: maleic anhydride grafted polymer: dioctyl phthalate = 95:8:3:10, chlorinated polyethylene rubber, polyurethane, maleic anhydride grafted polymer and dioctyl phthalate are mixed at 90°C to obtain modified chlorinated polyethylene rubber.
[0040] Among the above raw materials, the preparation method of the modified basalt fiber comprises the following steps: according to the mass ratio, basalt fiber: carbon black: potassium titanate whisker: fumed silica: propylene glycol laurate = 95:2:0.6:3:4, firstly, the potassium titanate whisker and the fumed silica are evenly mixed by air flow, and then the carbon black is added, and the air flow mixing is continued until uniform to obtain the auxiliary material; the propylene glycol laurate is diluted to 4.5 times the mass with ethanol to obtain the ball milling aid; the basalt fiber and the ball milling aid are wet-milled for 12 minutes, and then the auxiliary material is added, and the wet ball milling is continued for 15 minutes, the material is discharged, and the ethanol is removed by drying to obtain the modified basalt fiber.
[0041] In the above-mentioned method for preparing modified basalt fiber, the diameter of the basalt fiber ranges from 10 μm to 30 μm, and the length ranges from 1 mm to 3 mm.
[0042] In the above-mentioned method for preparing modified basalt fiber, the particle sizes of the carbon black, potassium titanate whiskers and fumed silica are all nanometer-level.
[0043] The above-mentioned method for preparing a high-strength wear-resistant polyethylene gas pipeline comprises the following steps:
[0044] S1: mixing silicon carbide ceramic material, magnesium oxide and lubricant according to weight proportions to obtain a mixture A;
[0045] S2: Mixing the hindered amine light stabilizer, the hindered phenol antioxidant and the antistatic agent according to their weight percentage to obtain a mixture B;
[0046] S3: Dry the high-density polyethylene at 90°C for 5 hours to remove moisture; add the high-density polyethylene, modified EPDM rubber, modified chlorinated polyethylene rubber, and mixture A into an internal mixer according to their mass fractions, and perform internal mixing at 150°C, with a rotation speed of 70r / min for 8 minutes; then add the modified basalt fiber and mixture B, perform internal mixing at 170°C, with a rotation speed of 110r / min for 18 minutes, and obtain the internal mixing material, which is extruded and molded by a single-screw or twin-screw extruder, and air-cooled to obtain a shaped pipe;
[0047] The extruder is divided into a feeding zone, a compression zone, a metering zone and a die zone: the temperature of the feeding zone is 145°C, the temperature of the compression zone is 175°C, the temperature of the metering zone is 165°C, and the temperature of the die zone is 155°C; the extrusion speed of the extruder is 1m / min;
[0048] S4, placing the shaped pipe at 55°C for 26 hours to obtain a finished pipe.
[0049] Example 2
[0050] A high-strength wear-resistant polyethylene gas pipeline comprises the following raw materials in parts by mass: 75 parts of high-density polyethylene, 6 parts of modified EPDM rubber, 3 parts of modified chlorinated polyethylene rubber, 8 parts of modified basalt fiber, 5 parts of silicon carbide ceramic material, 0.2 parts of magnesium oxide, 1.2 parts of lubricant, 0.2 parts of hindered amine light stabilizer, 0.1 parts of hindered phenol antioxidant, and 0.5 parts of antistatic agent.
[0051] Among them, the indicators of high-density polyethylene are: density 0.949g / cm 3 , crystallinity 80%, softening point 125°C. The lubricant includes calcium stearate, zinc stearate and silicone powder, and the mass ratio is calcium stearate: zinc stearate: silicone powder = 2:1:1. The silicon carbide ceramic material is a powder with a particle size of less than 50 μm obtained by crushing waste silicon carbide ceramics; the particle size of the magnesium oxide is less than 50 μm.
[0052] Among them, the preparation method of modified EPDM rubber includes the following steps: according to the mass ratio of EPDM rubber: polyurethane: maleic anhydride grafted polymer: dioctyl phthalate = 90:6:1:5, EPDM rubber, polyurethane, maleic anhydride grafted polymer and dioctyl phthalate are mixed at 65°C to obtain modified EPDM rubber.
[0053] Among the above raw materials, the preparation method of the modified chlorinated polyethylene rubber comprises the following steps: according to the mass ratio of chlorinated polyethylene rubber: polyurethane: maleic anhydride grafted polymer: dioctyl phthalate = 90:5:1:8, chlorinated polyethylene rubber, polyurethane, maleic anhydride grafted polymer and dioctyl phthalate are mixed at 85°C to obtain modified chlorinated polyethylene rubber.
[0054] Among the above raw materials, the preparation method of the modified basalt fiber comprises the following steps: according to the mass ratio, basalt fiber: carbon black: potassium titanate whisker: fumed silica: propylene glycol laurate = 90:1:0.4:2:3, firstly, the potassium titanate whisker and the fumed silica are evenly mixed by air flow, and then the carbon black is added, and the air flow mixing is continued until it is uniform to obtain the auxiliary material; the propylene glycol laurate is diluted to 4 times the mass with ethanol to obtain the ball milling aid; the basalt fiber and the ball milling aid are wet-milled for 10 minutes, and then the auxiliary material is added, and the wet ball milling is continued for 10 minutes, the material is discharged, and the ethanol is removed by drying to obtain the modified basalt fiber.
[0055] In the above-mentioned method for preparing modified basalt fiber, the diameter of the basalt fiber ranges from 10 μm to 30 μm, and the length ranges from 1 mm to 3 mm.
[0056] In the above-mentioned method for preparing modified basalt fiber, the particle sizes of the carbon black, potassium titanate whiskers and fumed silica are all nanometer-level.
[0057] The above-mentioned method for preparing a high-strength wear-resistant polyethylene gas pipeline comprises the following steps:
[0058] S1: mixing silicon carbide ceramic material, magnesium oxide and lubricant according to weight proportions to obtain a mixture A;
[0059] S2: Mixing the hindered amine light stabilizer, the hindered phenol antioxidant and the antistatic agent according to their weight percentage to obtain a mixture B;
[0060] S3: Dry the high-density polyethylene at 80°C for 4 hours to remove moisture; add the high-density polyethylene, modified EPDM rubber, modified chlorinated polyethylene rubber, and mixture A into an internal mixer according to their mass fractions, and perform internal mixing at 140°C, at a speed of 60r / min, for 5 minutes; then add the modified basalt fiber and mixture B, and perform internal mixing at 160°C, at a speed of 100r / min, for 15 minutes to obtain the internal mixing material, and extrude and mold it through a single-screw or twin-screw extruder, and air-cool it to obtain a shaped pipe;
[0061] The extruder is divided into a feeding zone, a compression zone, a metering zone and a die zone: the temperature of the feeding zone is 140°C, the temperature of the compression zone is 170°C, the temperature of the metering zone is 160°C, and the temperature of the die zone is 150°C; the extrusion speed of the extruder is 0.5m / min;
[0062] S4, placing the shaped pipe at 50°C for 24 hours to obtain a finished pipe.
[0063] Example 3
[0064] A high-strength wear-resistant polyethylene gas pipeline comprises the following raw materials in parts by mass: 75 parts of high-density polyethylene, 10 parts of modified EPDM rubber, 3 parts of modified chlorinated polyethylene rubber, 12 parts of modified basalt fiber, 5 parts of silicon carbide ceramic material, 0.6 parts of magnesium oxide, 1.2 parts of lubricant, 0.5 parts of hindered amine light stabilizer, 0.1 parts of hindered phenol antioxidant, and 1 part of antistatic agent.
[0065] Among them, the indicators of high-density polyethylene are: density 0.952g / cm 3 , crystallinity 82.3%, softening point 127°C. The lubricant includes calcium stearate, zinc stearate and silicone powder, and the mass ratio is calcium stearate: zinc stearate: silicone powder = 2:3:1. The silicon carbide ceramic material is a powder with a particle size of less than 50 μm obtained by crushing waste silicon carbide ceramics; the particle size of the magnesium oxide is less than 50 μm.
[0066] Among them, the preparation method of modified EPDM rubber includes the following steps: according to the mass ratio of EPDM rubber: polyurethane: maleic anhydride grafted polymer: dioctyl phthalate = 100:6:5:5, EPDM rubber, polyurethane, maleic anhydride grafted polymer and dioctyl phthalate are mixed at 75°C to obtain modified EPDM rubber.
[0067] Among the above raw materials, the preparation method of the modified chlorinated polyethylene rubber comprises the following steps: according to the mass ratio of chlorinated polyethylene rubber: polyurethane: maleic anhydride grafted polymer: dioctyl phthalate = 90:10:1:12, chlorinated polyethylene rubber, polyurethane, maleic anhydride grafted polymer and dioctyl phthalate are mixed at 85°C to obtain modified chlorinated polyethylene rubber.
[0068] Among the above raw materials, the preparation method of the modified basalt fiber comprises the following steps: according to the mass ratio, basalt fiber: carbon black: potassium titanate whisker: fumed silica: propylene glycol laurate = 100:1:0.8:2:5, firstly, the potassium titanate whisker and the fumed silica are evenly mixed by air flow, and then the carbon black is added, and the air flow mixing is continued until it is uniform to obtain the auxiliary material; the propylene glycol laurate is diluted to 4 times the mass with ethanol to obtain the ball milling aid; the basalt fiber and the ball milling aid are wet-milled for 15 minutes, and then the auxiliary material is added, and the wet ball milling is continued for 10 minutes, the material is discharged, and the ethanol is removed by drying to obtain the modified basalt fiber.
[0069] In the above-mentioned method for preparing modified basalt fiber, the diameter of the basalt fiber ranges from 10 μm to 30 μm, and the length ranges from 1 mm to 3 mm.
[0070] In the above-mentioned method for preparing modified basalt fiber, the particle sizes of the carbon black, potassium titanate whiskers and fumed silica are all nanometer-level.
[0071] The above-mentioned method for preparing a high-strength wear-resistant polyethylene gas pipeline comprises the following steps:
[0072] S1: mixing silicon carbide ceramic material, magnesium oxide and lubricant according to weight proportions to obtain a mixture A;
[0073] S2: Mixing the hindered amine light stabilizer, the hindered phenol antioxidant and the antistatic agent according to their weight percentage to obtain a mixture B;
[0074] S3: Dry the high-density polyethylene at 95°C for 4 hours to remove moisture; add the high-density polyethylene, modified EPDM rubber, modified chlorinated polyethylene rubber, and mixture A into an internal mixer according to their mass fractions, and perform internal mixing at 160°C, with a speed of 60r / min for 10min; then add the modified basalt fiber and mixture B, and perform internal mixing at 160°C, with a speed of 120r / min for 15min to obtain the internal mixing material, and extrude and mold it through a single-screw or twin-screw extruder, and air-cool it to obtain a shaped pipe;
[0075] The extruder is divided into a feeding zone, a compression zone, a metering zone and a die zone: the temperature of the feeding zone is 150°C, the temperature of the compression zone is 170°C, the temperature of the metering zone is 170°C, and the temperature of the die zone is 150°C; the extrusion speed of the extruder is 1.5m / min;
[0076] S4, placing the shaped pipe at 50°C for 30 hours to obtain a finished pipe.
[0077] Example 4
[0078] A high-strength wear-resistant polyethylene gas pipeline comprises the following raw materials in parts by mass: 85 parts of high-density polyethylene, 10 parts of modified EPDM rubber, 5 parts of modified chlorinated polyethylene rubber, 12 parts of modified basalt fiber, 8 parts of silicon carbide ceramic material, 0.6 parts of magnesium oxide, 2 parts of lubricant, 0.5 parts of hindered amine light stabilizer, 0.5 parts of hindered phenol antioxidant, and 1 part of antistatic agent.
[0079] Among them, the indicators of high-density polyethylene are: density 0.965g / cm 3 , crystallinity 90%, softening point 135°C. The lubricant includes calcium stearate, zinc stearate and silicone powder, and the mass ratio is calcium stearate: zinc stearate: silicone powder = 5:3:3. The silicon carbide ceramic material is a powder with a particle size of less than 50 μm obtained by crushing waste silicon carbide ceramics; the particle size of the magnesium oxide is less than 50 μm.
[0080] Among them, the preparation method of modified EPDM rubber includes the following steps: according to the mass ratio of EPDM rubber: polyurethane: maleic anhydride grafted polymer: dioctyl phthalate = 100:12:5:10, EPDM rubber, polyurethane, maleic anhydride grafted polymer and dioctyl phthalate are mixed at 75°C to obtain modified EPDM rubber.
[0081] Among the above raw materials, the preparation method of the modified chlorinated polyethylene rubber comprises the following steps: according to the mass ratio of chlorinated polyethylene rubber: polyurethane: maleic anhydride grafted polymer: dioctyl phthalate = 100:10:5:12, chlorinated polyethylene rubber, polyurethane, maleic anhydride grafted polymer and dioctyl phthalate are mixed at 95°C to obtain modified chlorinated polyethylene rubber.
[0082] Among the above raw materials, the preparation method of the modified basalt fiber comprises the following steps: according to the mass ratio, basalt fiber: carbon black: potassium titanate whisker: fumed silica: propylene glycol laurate = 100:3:0.8:5:5, firstly, the potassium titanate whisker and the fumed silica are evenly mixed by air flow, and then the carbon black is added, and the air flow mixing is continued until uniform to obtain the auxiliary material; the propylene glycol laurate is diluted to 5 times the mass with ethanol to obtain the ball milling aid; the basalt fiber and the ball milling aid are wet-milled for 15 minutes, and then the auxiliary material is added, and the wet ball milling is continued for 20 minutes, the material is discharged, and the ethanol is removed by drying to obtain the modified basalt fiber.
[0083] In the above-mentioned method for preparing modified basalt fiber, the diameter of the basalt fiber ranges from 10 μm to 30 μm, and the length ranges from 1 mm to 3 mm.
[0084] In the above-mentioned method for preparing modified basalt fiber, the particle sizes of the carbon black, potassium titanate whiskers and fumed silica are all nanometer-level.
[0085] The above-mentioned method for preparing a high-strength wear-resistant polyethylene gas pipeline comprises the following steps:
[0086] S1: mixing silicon carbide ceramic material, magnesium oxide and lubricant according to weight proportions to obtain a mixture A;
[0087] S2: Mixing the hindered amine light stabilizer, the hindered phenol antioxidant and the antistatic agent according to their weight percentage to obtain a mixture B;
[0088] S3: Dry the high-density polyethylene at 95°C for 6 hours to remove moisture; add the high-density polyethylene, modified EPDM rubber, modified chlorinated polyethylene rubber, and mixture A into an internal mixer according to their mass fractions, and perform internal mixing at 160°C, with a speed of 80r / min for 10min; then add the modified basalt fiber and mixture B, and perform internal mixing at 180°C, with a speed of 120r / min for 20min to obtain the internal mixing material, and extrude and mold it through a single-screw or twin-screw extruder, and air-cool it to obtain a shaped pipe;
[0089] The extruder is divided into a feeding zone, a compression zone, a metering zone and a die zone: the temperature of the feeding zone is 150°C, the temperature of the compression zone is 180°C, the temperature of the metering zone is 170°C, and the temperature of the die zone is 160°C; the extrusion speed of the extruder is 1.5m / min;
[0090] S4, placing the shaped pipe at 60°C for 30 hours to obtain a finished pipe.
[0091] Example 5
[0092] A high-strength wear-resistant polyethylene gas pipeline comprises the following raw materials in parts by mass: 85 parts of high-density polyethylene, 6 parts of modified EPDM rubber, 5 parts of modified chlorinated polyethylene rubber, 8 parts of modified basalt fiber, 8 parts of silicon carbide ceramic material, 0.2 parts of magnesium oxide, 2 parts of lubricant, 0.2 parts of hindered amine light stabilizer, 0.5 parts of hindered phenol antioxidant, and 0.5 parts of antistatic agent.
[0093] Among them, the indicators of high-density polyethylene are: density 0.960g / cm 3 , crystallinity 86.8%, softening point 131°C. The lubricant includes calcium stearate, zinc stearate and silicone powder, and the mass ratio is calcium stearate: zinc stearate: silicone powder = 5:1:3. The silicon carbide ceramic material is a powder with a particle size of less than 50 μm obtained by crushing waste silicon carbide ceramics; the particle size of the magnesium oxide is less than 50 μm.
[0094] Among them, the preparation method of modified EPDM rubber includes the following steps: according to the mass ratio of EPDM rubber: polyurethane: maleic anhydride grafted polymer: dioctyl phthalate = 90:12:1:10, EPDM rubber, polyurethane, maleic anhydride grafted polymer and dioctyl phthalate are mixed at 65°C to obtain modified EPDM rubber.
[0095] Among the above raw materials, the preparation method of the modified chlorinated polyethylene rubber comprises the following steps: according to the mass ratio of chlorinated polyethylene rubber: polyurethane: maleic anhydride grafted polymer: dioctyl phthalate = 100:5:5:8, chlorinated polyethylene rubber, polyurethane, maleic anhydride grafted polymer and dioctyl phthalate are mixed at 95°C to obtain modified chlorinated polyethylene rubber.
[0096] Among the above raw materials, the preparation method of the modified basalt fiber comprises the following steps: according to the mass ratio, basalt fiber: carbon black: potassium titanate whisker: fumed silica: propylene glycol laurate = 90:3:0.4:5:3, firstly, the potassium titanate whisker and the fumed silica are evenly mixed by air flow, and then the carbon black is added, and the air flow mixing is continued until it is uniform to obtain the auxiliary material; the propylene glycol laurate is diluted to 5 times the mass with ethanol to obtain the ball milling aid; the basalt fiber and the ball milling aid are wet-milled for 10 minutes, and then the auxiliary material is added, and the wet ball milling is continued for 20 minutes, the material is discharged, and the ethanol is removed by drying to obtain the modified basalt fiber.
[0097] In the above-mentioned method for preparing modified basalt fiber, the diameter of the basalt fiber ranges from 10 μm to 30 μm, and the length ranges from 1 mm to 3 mm.
[0098] In the above-mentioned method for preparing modified basalt fiber, the particle sizes of the carbon black, potassium titanate whiskers and fumed silica are all nanometer-level.
[0099] The above-mentioned method for preparing a high-strength wear-resistant polyethylene gas pipeline comprises the following steps:
[0100] S1: mixing silicon carbide ceramic material, magnesium oxide and lubricant according to weight proportions to obtain a mixture A;
[0101] S2: Mixing the hindered amine light stabilizer, the hindered phenol antioxidant and the antistatic agent according to their weight percentage to obtain a mixture B;
[0102] S3: Dry the high-density polyethylene at 80°C for 6 hours to remove moisture; add the high-density polyethylene, modified EPDM rubber, modified chlorinated polyethylene rubber, and mixture A into an internal mixer according to their mass fractions, and perform internal mixing at 140°C, with a speed of 80r / min for 5 minutes; then add the modified basalt fiber and mixture B, and perform internal mixing at 180°C, with a speed of 100r / min for 20 minutes to obtain the internal mixing material, and extrude and mold it through a single-screw or twin-screw extruder, and air-cool it to obtain a shaped pipe;
[0103] The extruder is divided into a feeding zone, a compression zone, a metering zone and a die zone: the temperature of the feeding zone is 145°C, the temperature of the compression zone is 172°C, the temperature of the metering zone is 164°C, and the temperature of the die zone is 156°C; the extrusion speed of the extruder is 1.2m / min;
[0104] S4, placing the shaped pipe at 55°C for 28 hours to obtain a finished pipe.
[0105] Example 6
[0106] A high-strength wear-resistant polyethylene gas pipeline comprises the following raw materials in parts by mass: 82 parts of high-density polyethylene, 7 parts of modified EPDM rubber, 3.5 parts of modified chlorinated polyethylene rubber, 11 parts of modified basalt fiber, 6 parts of silicon carbide ceramic material, 0.3 parts of magnesium oxide, 1.5 parts of lubricant, 0.4 parts of hindered amine light stabilizer, 0.3 parts of hindered phenol antioxidant, and 0.6 parts of antistatic agent.
[0107] Among them, the indicators of high-density polyethylene are: density 0.957g / cm 3 , crystallinity 84.7%, softening point 129°C. The lubricant includes calcium stearate, zinc stearate and silicone powder, and the mass ratio is calcium stearate: zinc stearate: silicone powder = 4:1:3. The silicon carbide ceramic material is a powder with a particle size of less than 50 μm obtained by crushing waste silicon carbide ceramics; the particle size of the magnesium oxide is less than 50 μm.
[0108] Among them, the preparation method of modified EPDM rubber includes the following steps: according to the mass ratio of EPDM rubber: polyurethane: maleic anhydride grafted polymer: dioctyl phthalate = 98:8:4:6, EPDM rubber, polyurethane, maleic anhydride grafted polymer and dioctyl phthalate are mixed at 72°C to obtain modified EPDM rubber.
[0109] Among the above raw materials, the preparation method of the modified chlorinated polyethylene rubber comprises the following steps: according to the mass ratio of chlorinated polyethylene rubber: polyurethane: maleic anhydride grafted polymer: dioctyl phthalate = 95:8:4:9, chlorinated polyethylene rubber, polyurethane, maleic anhydride grafted polymer and dioctyl phthalate are mixed at 92°C to obtain modified chlorinated polyethylene rubber.
[0110] Among the above raw materials, the preparation method of the modified basalt fiber comprises the following steps: according to the mass ratio, basalt fiber: carbon black: potassium titanate whisker: fumed silica: propylene glycol laurate = 94:2:0.5:3:3, firstly, the potassium titanate whisker and the fumed silica are evenly mixed by air flow, and then the carbon black is added, and the air flow mixing is continued until uniform to obtain the auxiliary material; the propylene glycol laurate is diluted to 5 times the mass with ethanol to obtain the ball milling aid; the basalt fiber and the ball milling aid are wet-milled for 10 minutes, and then the auxiliary material is added, and the wet ball milling is continued for 15 minutes, the material is discharged, and the ethanol is removed by drying to obtain the modified basalt fiber.
[0111] In the above-mentioned method for preparing modified basalt fiber, the diameter of the basalt fiber ranges from 10 μm to 30 μm, and the length ranges from 1 mm to 3 mm.
[0112] In the above-mentioned method for preparing modified basalt fiber, the particle sizes of the carbon black, potassium titanate whiskers and fumed silica are all nanometer-level.
[0113] The above-mentioned method for preparing a high-strength wear-resistant polyethylene gas pipeline comprises the following steps:
[0114] S1: mixing silicon carbide ceramic material, magnesium oxide and lubricant according to weight proportions to obtain a mixture A;
[0115] S2: Mixing the hindered amine light stabilizer, the hindered phenol antioxidant and the antistatic agent according to their weight percentage to obtain a mixture B;
[0116] S3: Dry the high-density polyethylene at 95°C for 5 hours to remove moisture; add the high-density polyethylene, modified EPDM rubber, modified chlorinated polyethylene rubber, and mixture A into an internal mixer according to their mass fractions, and perform internal mixing at 155°C, with a speed of 80r / min for 6 minutes; then add the modified basalt fiber and mixture B, and perform internal mixing at 175°C, with a speed of 120r / min for 15 minutes to obtain the internal mixing material, and extrude it into shape through a single-screw or twin-screw extruder, and air-cool it to obtain a shaped pipe;
[0117] The extruder is divided into a feeding zone, a compression zone, a metering zone and a die zone: the temperature of the feeding zone is 150°C, the temperature of the compression zone is 175°C, the temperature of the metering zone is 168°C, and the temperature of the die zone is 155°C; the extrusion speed of the extruder is 0.8m / min;
[0118] S4, placing the shaped pipe at 55°C for 28 hours to obtain a finished pipe.
[0119] The model of the high-density polyethylene used in the above embodiments is 5000S, Suzhou Sutu Plastic New Material Co., Ltd.; the model of the hindered amine light stabilizer is UV-770, Dongguan Kangjin New Material Technology Co., Ltd.; the model of the hindered phenol antioxidant is Y-1010, Dongguan Kangjin New Material Technology Co., Ltd.; the model of the maleic anhydride grafted polymer is 9901, Dongguan Kangjin New Material Technology Co., Ltd.; the model of the antistatic agent is ZR-550, Shanghai Zirun Chemical Additive Co., Ltd.; the model of the EPDM rubber is 3080P, Jilin Petrochemical Branch of China National Petroleum Corporation; the model of the chlorinated polyethylene rubber is CPE-135A, Shijiazhuang Duobo Chemical Technology Co., Ltd.
[0120] Comparative Example 1
[0121] The EPDM rubber is not modified; the modified EPDM rubber is replaced by EPDM rubber; other methods and parameters are the same as in Example 1.
[0122] Comparative Example 2
[0123] The chlorinated polyethylene rubber is not modified; the modified chlorinated polyethylene rubber is replaced by chlorinated polyethylene rubber; other methods and parameters are the same as in Example 1.
[0124] Comparative Example 3
[0125] Neither EPDM rubber nor chlorinated polyethylene rubber is modified; modified EPDM rubber is replaced by EPDM rubber, and modified chlorinated polyethylene rubber is replaced by chlorinated polyethylene rubber; other methods and parameters are the same as in Example 1.
[0126] Comparative Example 4
[0127] The EPDM rubber was modified without adding polyurethane and dioctyl phthalate; the chlorinated polyethylene rubber was modified without adding polyurethane and dioctyl phthalate; other methods and parameters were the same as in Example 1.
[0128] Comparative Example 5
[0129] The basalt fiber is not modified, and the modified basalt fiber is replaced by basalt fiber; other methods and parameters are the same as in Example 1.
[0130] Comparative Example 6
[0131] In the preparation method of the modified basalt fiber, propylene glycol laurate is not added, and ball milling aid is not prepared, that is, dry ball milling is used for modification; other methods and parameters are the same as in Example 1.
[0132] Comparative Example 7
[0133] In the preparation method of the modified basalt fiber, fumed silica and propylene glycol laurate are not added, and a ball milling aid is not prepared, that is, dry ball milling is used for modification; other methods and parameters are the same as in Example 1.
[0134] Comparative Example 8
[0135] No magnesium oxide was added to the raw materials, and no silicone powder was added to the lubricant; in 1.6 parts of the lubricant, the mass ratio was calcium stearate: zinc stearate = 3:2; other methods and parameters were the same as in Example 1.
[0136] Comparative Example 9
[0137] The EPDM rubber, chlorinated polyethylene rubber and basalt fiber were not modified in advance; the improvers such as polyurethane, maleic anhydride grafted polymer, dioctyl phthalate, carbon black, potassium titanate whisker, fumed silica and propylene glycol laurate were directly involved in the mixing and kneading of the mixture A, and the other methods and parameters were the same as those in Example 1.
[0138] Comparative Example 10
[0139] The conventional polyethylene gas pipes on the market (polyethylene accounts for 96%) have an outer diameter of 32mm and a thickness of 4mm.
[0140] The materials of the above-mentioned embodiments and comparative examples were prepared into test samples and the following performance tests were carried out.
[0141] (1) Wear resistance test method: Prepare the extruded sample with a thickness of 4 mm on a flat plate; use a wear tester with an H-18 grinding wheel, apply a load of 800 g, rotate at a speed of 60 r / min, and rotate for a total of 800 revolutions; make three parallel samples for each type; weigh them before and after the test, and calculate the weight loss rate. The smaller the weight loss rate, the better the wear resistance.
[0142] (2) Compressive strength test method: The sample specification is a pipe with an outer diameter of 32 mm and a thickness of 4 mm. The compressive deformation strength is tested using a pressure testing machine. Three parallel samples are made for each type.
[0143] (3) Impact resistance test method: The sample specification is a pipe with an outer diameter of 32mm and a thickness of 4mm. The test is carried out according to the drop hammer method of GB / T14152, with a drop hammer weight of 12kg and 14kg and a height of 2m. Ten parallel samples are made for each type, and the number of cracks is counted.
[0144] (4) Hardness test method: The sample specification is a pipe with an outer diameter of 32 mm and a thickness of 4 mm. The hardness test is carried out using a Shore D hardness tester. Three parallel samples are made for each type.
[0145] (5) Tensile strength test method: The sample specification is a pipe with an outer diameter of 32 mm and a thickness of 4 mm. A universal material testing machine is used for tensile strength testing. Three parallel samples are made for each type.
[0146] (6) Elongation at break test method: The sample specification is a pipe with an outer diameter of 32 mm and a thickness of 4 mm. The elongation at break test is carried out using a universal material testing machine. Three parallel samples are made for each type.
[0147] (7) Weathering resistance test method: The sample specification is a pipe with an outer diameter of 32mm and a thickness of 4mm; 3 sections of each pipe are taken and subjected to light aging in a xenon arc lamp aging test chamber with a light intensity of 0.55W / m² / nm (340nm); temperature: 50℃; humidity: 70%; water is sprayed for 10 minutes every 2 hours; after 30 days, compressive strength, hardness, tensile strength, and elongation at break are tested; the change rate of compressive strength, hardness, tensile strength, and elongation at break after aging is calculated to evaluate weathering resistance. Change rate (reduction rate) = (value before the experiment - value after the experiment) / value before the experiment × 100%.
[0148] The average detection results are shown in Tables 1 and 2 below.
[0149] Table 1 Test results of the embodiment
[0150]
[0151] It can be seen from the above results that the samples of Examples 1 to 6 have good wear resistance, and have high compressive strength, impact resistance, tensile strength, weather resistance and other indicators; they can effectively improve the performance and service life of the pipeline.
[0152] Table 2 Comparative Example Test Results
[0153]
[0154] By comparing the results of Comparative Examples 1 to 3 with the results of Example 1, it can be seen that the modification of EPDM rubber and chlorinated polyethylene rubber with polyurethane, maleic anhydride grafted polymer and dioctyl phthalate respectively can improve the various properties of the pipeline; the modified EPDM rubber and modified chlorinated polyethylene rubber can greatly enhance the performance of the pipeline, and have a synergistic effect. By comparing the results of Comparative Example 4 with the results of Example 1, it can be seen that the modification of polyurethane and dioctyl phthalate can enhance the strength and wear resistance of the rubber component, and the strength and wear resistance of polyethylene can be further improved after mixing and kneading, thereby improving the strength and wear resistance of the pipeline. By comparing the results of Comparative Example 5 with the results of Example 1, it can be seen that the composite surface modification of basalt fiber using carbon black, potassium titanate whiskers, fumed silica and propylene glycol laurate can greatly improve the mechanical properties of basalt fiber, as well as the mechanical properties of plastic and rubber components with a small amount. By comparing the results of Comparative Example 6 with those of Example 1, it can be seen that the preparation of ball milling aid with propylene glycol laurate can improve the modified quality of basalt, and the modified homogeneity is better. After adding banburying, the distribution of basalt is more uniform, which can effectively reduce the generation of weak parts of the pipeline, thereby improving the mechanical properties of the pipeline. By comparing the results of Comparative Example 7 with those of Example 1, it can be seen that the combination of fumed silica and propylene glycol laurate has better improvement in the uniformity of modified distribution, pipeline homogeneity, and comprehensive performance, and fumed silica has the effect of further enhancing pipeline performance. By comparing the results of Comparative Example 8 with those of Example 1, it can be seen that the combination of magnesium oxide and silicone powder has a good effect on enhancing the mechanical properties of rubber and polyethylene plastics. By comparing the results of Comparative Example 9 with those of Example 1, it can be seen that the unmodified EPDM rubber, chlorinated polyethylene rubber, and basalt fiber are not modified in advance, and all modified raw materials are directly mixed and kneaded, resulting in poor homogeneity of the obtained pipe material, and the performance enhancement effect of the modifier on EPDM rubber, chlorinated polyethylene rubber, and basalt fiber is greatly weakened, especially the mechanical properties of basalt fiber are weakened, resulting in a significant decrease in various performances of the pipe. By comparing the results of Comparative Example 10 with those of Example 1, it can be seen that the gas pipeline of the present invention has a very outstanding performance effect compared with the conventional polyethylene gas pipeline, can greatly extend the service life, and is more suitable for use in various harsh environments.
Claims
1. A high-strength wear-resistant polyethylene gas pipeline, characterized in that: The pipeline includes the following raw materials in parts by weight: 75 to 85 parts of high-density polyethylene, 6 to 10 parts of modified EPDM rubber, 3 to 5 parts of modified chlorinated polyethylene rubber, 8 to 12 parts of modified basalt fiber, 5 to 8 parts of silicon carbide ceramic material, 0.2 to 0.6 parts of magnesium oxide, 1.2 to 2 parts of lubricant, 0.2 to 0.5 parts of hindered amine light stabilizer, 0.1 to 0.5 parts of hindered phenol antioxidant, and 0.5 to 1 parts of antistatic agent; The preparation method of the modified EPDM rubber comprises the following steps: mixing the EPDM rubber, the polyurethane, the maleic anhydride grafted polymer and the dioctyl phthalate at 65° C. to 75° C. in a mass ratio of EPDM rubber: polyurethane: maleic anhydride grafted polymer: dioctyl phthalate = (90 to 100): (6 to 12): (1 to 5): (5 to 10) to obtain the modified EPDM rubber; The preparation method of the modified chlorinated polyethylene rubber comprises the following steps: mixing the chlorinated polyethylene rubber, polyurethane, maleic anhydride grafted polymer and dioctyl phthalate at 85° C. to 95° C. in a mass ratio of chlorinated polyethylene rubber: polyurethane: maleic anhydride grafted polymer: dioctyl phthalate = (90 to 100): (5 to 10): (1 to 5): (8 to 12) to obtain the modified chlorinated polyethylene rubber; The preparation method of the modified basalt fiber comprises the following steps: according to the mass ratio of basalt fiber: carbon black: potassium titanate whisker: fumed silica: propylene glycol laurate = (90-100): (1-3): (0.4-0.8): (2-5): (3-5), firstly, the potassium titanate whisker and the fumed silica are uniformly mixed by air flow, then the carbon black is added, and the air flow mixing is continued until uniform to obtain an auxiliary material; the propylene glycol laurate is diluted to 4 to 5 times the mass by ethanol to obtain a ball milling aid; the basalt fiber and the ball milling aid are wet-milled for 10 to 15 minutes, then the auxiliary material is added, the wet-milling is continued for 10 to 20 minutes, the material is discharged, and the ethanol is removed by drying to obtain the modified basalt fiber.
2. A high-strength wear-resistant polyethylene gas pipeline according to claim 1, characterized in that: The index of the high-density polyethylene is: density 0.949g / cm 3 ~0.965g / cm 3 , crystallinity 80%~90%, softening point 125℃~135℃.
3. The high-strength wear-resistant polyethylene gas pipeline according to claim 1, characterized in that: The lubricant comprises calcium stearate, zinc stearate and silicone powder, and the mass ratio of calcium stearate:zinc stearate:silicone powder is (2-5):(1-3):(1-3).
4. The high-strength wear-resistant polyethylene gas pipeline according to claim 1, characterized in that: The silicon carbide ceramic material is a powder obtained by crushing waste silicon carbide ceramics to obtain a particle size of less than 50 μm; the particle size of the magnesium oxide is less than 50 μm.
5. The high-strength wear-resistant polyethylene gas pipeline according to claim 1, characterized in that: The diameter of the basalt fiber is in the range of 10 μm to 30 μm, and the length is in the range of 1 mm to 3 mm; the particle sizes of the carbon black, potassium titanate whisker and fumed silica are all in nanometer level.
6. A method for preparing a high-strength wear-resistant polyethylene gas pipeline, used for preparing the high-strength wear-resistant polyethylene gas pipeline according to claim 1, characterized in that: The preparation method comprises the following steps: S1: mixing silicon carbide ceramic material, magnesium oxide and lubricant according to weight proportions to obtain a mixture A; S2: Mixing the hindered amine light stabilizer, the hindered phenol antioxidant and the antistatic agent according to their weight percentage to obtain a mixture B; S3: Dry the high-density polyethylene to remove moisture; add the high-density polyethylene, modified EPDM rubber, modified chlorinated polyethylene rubber, and mixture A into an internal mixer according to the mass fraction, and perform internal mixing at 140°C to 160°C, with a rotation speed of 60r / min to 80r / min, for 5min to 10min, then add the modified basalt fiber and mixture B, perform internal mixing at 160°C to 180°C, with a rotation speed of 100r / min to 120r / min, for 15min to 20min, and obtain the internal mixing material, and extrude and shape it through a single-screw or twin-screw extruder, and air-cool it to obtain a shaped pipe; S4, placing the shaped pipe at 50℃~60℃ and leaving it to stand for 24h~30h to obtain a finished pipe.
7. The method for preparing a high-strength wear-resistant polyethylene gas pipeline according to claim 6, characterized in that: In S3, the drying temperature is 80℃~95℃, and the drying time is 4h~6h; in S3, the extruder is divided into a feeding zone, a compression zone, a metering zone and a head zone: the temperature of the feeding zone is 140℃~150℃, the temperature of the compression zone is 170℃~180℃, the temperature of the metering zone is 160℃~170℃, and the temperature of the head zone is 150℃~160℃; the extrusion speed of the extruder is 0.5m / min~1.5m / min.
Citation Information
Patent Citations
High-density polyethylene composite material and preparation method thereof
CN114479237A
Fiber-reinforced buried drainage pipeline material and preparation method thereof
CN116656030A